Effect of silicon application on vegetative growth, flowering and corm production in gladiolus (Gladiolus hybridus Hort.) - SAMEER; KUMAR, RAKESH; SINGH , AJAY KUMAR; KANAWJIA, AMIT (Journal of Ornamental Horticulture, 2024)
An experiment was carried out to study the "Effect of silicon application on vegetative growth, flowering and corm production in gladiolus (Gladiolus hybridus Hort.)" under Bundelkhand conditions of Uttar Pradesh. The experiment was laid out in Factorial Randomized Block Design with three replications at Department of Floriculture & Landscape Architecture, College of Horticulture, Banda University of Agriculture and Technology, Banda during October, 2022 to April, 2023. In the experiment, soil application of silicon (2.9, 5.9 and 8.8 g/m2) was done before planting and foliar application of silicon was done @ 1% (4.7 g/m2) and 2% (9.4 g/m2) at 3 and 6-leaf stage. Analysis of results revealed that among different soil application treatments, S4 treatment (8.8 g/m2) obtained best results for leaf area (63.01 cm2), number of florets per spike (13.42), floret size (9.99 cm), rachis length (52.51 cm), fresh weight of spike (59.01 g), vase life (13.22 days) and weight of corm per plant (20.70 g). However, among foliar application treatments of silicon i.e., F3 treatment (2% silicon application) recorded maximum leaf area (63.83 cm2) and weight of corm per plant (20.25 g). Whereas, maximum number of cormels per plant (69.79) and water uptake (85.00 ml) was recorded in F1 (control). Among the different treatment combinations of soil and foliar application of silicon, S4F1 treatment combination recorded maximum plant height at 75 DAP (58.90 cm), number of florets per spike (13.87), rachis length (55.82 cm) and duration of flowering (15.73 days). Whereas, maximum leaf area (67.26 cm2), vase life (13.50 days) and weight of cormels per plant (16.73 g) was recorded in S4F3 treatment combination.